Keeping a modeling-driven public health dashboard relevant—lessons learned from the California Communicable diseases Assessment Tool - Thakur, Mugdha; White, Lauren A.; Pugliese, John; Crow, David; Lu, Phoebe; Linton, Natalie; McCorvie, Ryan; Ravuri, Sindhu; Sánchez C., Hector M.; Siegel, Brent; Vargo, Jason; León, Tomás M. (Frontiers in Public Health, 2025)
Researchers rapidly developed modeling-based dashboards to support the global COVID-19 pandemic response, and this output has continued for other public health responses. These dashboards are often abandoned or deprecated over time, creating challenges for public health jurisdictions that would like to leverage them for decision-making. Maintaining a relevant and sustainable dashboard requires significant effort and attention to collating modeling results and meeting local public health needs. The California Communicable diseases Assessment Tool (CalCAT), a public-facing infectious disease modeling dashboard, demonstrates the key components to sustainability and relevance: robust and flexible workflows, cultivation of trust and user engagement, wide-ranging collaboration, and content reproducibility. The experience of CalCAT’s initiation and development highlights the need to be responsive to ever-changing stakeholder requests and to balance trade-offs in design choices for how modeling results are processed, presented, and shared.